Immediate versus early soft tissue coverage for severe open grade III B tibia fractures: a comparative clinical study - Jain, Karun (International Journal of Research in Orthopaedics, 2024)
Controversy remains regarding timing in the management of grade III-B open tibia fractures. Many authors recommend an immediate definitive soft tissue coverage within a critical period of 12 hours, yet in many patients, this may be impossible due to concomitant injuries or delayed referral. The present case series aims to compare the role of immediate versus early soft tissue coverage for severe open grade III-B tibial fractures. 20 cases of tibial fractures of were divided into two groups; 10 cases each. Immediate group (within 12 hours) and early group (3-7 days), according to the soft tissue coverage time. Strict criteria for inclusion in the first group included debridement within 12 hours of injury, no sewage or organic contamination, the presence of bleeding skin margins, and the absence of systemic illness. All 20 cases had been treated by a debridement and soft-tissue cover with a muscle pedicle or fasio-cutanous flap. Functional outcome measures included deep infection rate, stable soft tissue coverage, number of inpatient’s stays, number of surgical procedures, and union time. The mean follow-up period was 24 months. Mean inpatient time was 30 and 41 days respectively. Mean surgical procedures were 2.2 and 3.4 respectively and union time was 26 versus 34 weeks. Mean inpatient time, mean surgical procedures per time and union time were pointedly less in the immediate flap coverage group which significantly improves results concerning early union, healing time, and cost of hospitalization and rehabilitation.